Once-daily amoxicillin versus twice-daily penicillin V in group A β-haemolytic streptococcal pharyngitis. Issue 6 (12th March 2008) - Lennon, D R; Farrell, E; Martin, D R; Stewart, J M
Abstract : Background: Rheumatic fever is a preventable chronic disease preceded by group A β-haemolytic streptococcal (GABHS) pharyngitis. Objective: To test the non-inferiority of once-daily (QD) oral amoxicillin to the recommended twice-daily (BID) oral penicillin V in GABHS pharyngitis. Methods: This was a randomised non-inferiority trial carried out in a school-based clinic in New Zealand. Children presenting with GABHS pharyngitis were randomised to oral amoxicillin 1500 mg QD (or 750 mg if bodyweight was ⩽30 kg) or to oral penicillin V 500 mg BID (or 250 mg if bodyweight was ⩽20 kg) for 10 days. Observed medication and weekend diary cards were used to monitor adherence. Outcome: Eradication of GABHS, determined with follow-up throat cultures on days 3–6, 12–16 and 26–36. GABHS isolates were serotyped to distinguish bacteriological treatment failures (and relapses) from new acquisitions. Non-inferiority was defined as an upper 95% confidence limit (CL) for the difference in success of eradication in the amoxicillin and penicillin V treatment groups of ⩽10%. Results: 353 children with positive throat swabs for GABHS were randomised to amoxicillin (n = 177) or penicillin V (n = 176). The upper 95% CL for the differences in positive cultures between the antibiotics was 4.9% at days 3–6, 6.5% at days 12–16 and 8.5% at days 26–36. Treatment failures (including relapses) occurred at each visit in 5.8%, 12.7% and 10.7% of amoxicillin recipients and 6.2%, 11.9% and 11.3% of penicillin V recipients, respectively. No significant differences in resolution of symptoms were noted between treatment groups. One case of unsubstantiated acute rheumatic fever occurred after 7 days of amoxicillin. Conclusion: In this adequately powered study, once-daily oral amoxicillin is not inferior to twice-daily penicillin V for the treatment and eradication of GABHS in children with pharyngitis.